Achilles Subtendon Structure and Behavior as Evidenced From Tendon Imaging and Computational Modeling - Handsfield, Geoffrey G.; Greiner, Joachim; Madl, Josef; Rog-Zielinska, Eva A.; Hollville, Enzo; Vanwanseele, Benedicte; Shim, Vickie (Frontiers in Sports and Active Living, 2020)
The Achilles tendon is the largest and strongest tendon in the human body and is essential for storing elastic energy and positioning the foot for walking and running. Recent research into Achilles tendon anatomy and mechanics has revealed the importance of the Achilles subtendons, which are unique and semi-independent structures arising from each of the three muscular heads of the triceps surae. Of particular importance is the ability for the subtendons to slide, the role that this has in healthy tendons, and the alteration of this property in aging and disease. In this work, we discuss technical approaches that have led to the current understanding of Achilles subtendons, particularly imaging and computational modeling. We introduce a 3D geometrical model of the Achilles subtendons, built from dual-echo UTE MRI. We revisit and discuss computational models of Achilles subtendon twisting suggesting that optimal twist reduces both rupture loads and stress concentrations by distributing stresses. Second harmonic generation imaging shows collagenous subtendons within a rabbit Achilles tendon; a clear absence of signal between the subtendons indicates an inter-subtendon region on the order of 30 μm in our rabbit animal model. Entry of wheat germ agglutinin in both the inter-fascicular and the inter-subtendon regions suggests a glycoprotein-containing inter-subtendon matrix which may facilitate low friction sliding of the subtendons in healthy mammals. Lastly, we present a new computational model coupled with human exercise trials to demonstrate the magnitude of Achilles subtendon sliding which occurs during rehabilitation exercises for Achilles tendinopathy, and shows that specific exercise can maximize subtendon sliding and interface strains, without maximizing subtendon strains. This work demonstrates the value of imaging and computational modeling for probing tendon structure-function relationships and may serve to inform and develop treatments for Achilles tendinopathy.